O jovem autor de ato infracional e a educação escolar : significados, desafios e caminhos para a permanência na escola - Dias, Aline Fávaro (Universidade Federal de São Carlos, 2011)
The legal achievements that reassure the rights for children and young people, especially the right to education, are in need of the public actions concerning democratization of school access and attendance of young offenders. The school failure and abandonment are a common phenomenon in young offenders lives, and a significant percentage of these young do not attend to school. This qualitative study has as its central objective to comprehend the significance that young who currently attend to an assisted freedom attribute to school and their scholar experiences, aiming to identify the aspects which might act as facilitators and obstacles for their school attendance. The study included six young offenders who currently attend to an assisted freedom. The data collect were carried out by means of semi-structured interviews, observation with diary registration and documental analysis. It was found that school history of the young participants are marked by frequent changes of schools, school failures and expulsions, with the institution an ambiguous meaning, because while it discriminates, label and is the scene of conflict with teachers and peers, also promotes sociability, relationships friendship and flirting. In general, the narrative of young people about school indicates that this space is present violence and resistance movements against the relationships that oppress them, but also social relationships between friends and teachers. Overcome the idea of banking education, starting with the knowledge of experience had the students, respecting their way of being in the world, promoting inquiry, research, criticism and awareness of the reality around them, perceived themselves as routes to be followed in facing the difficulties pointed out by young people to their school attendance. The study highlights the need for training of educators in their classrooms to promote a more humane and liberating education, and that the improvement of interpersonal relationships in school constitutes a way to promote school attendance of young offenders who currently attend to an assisted freedom.
Young offender and school education: meanings, challenges and ways for school attendance
Keywords: Delinquência juvenil; Educação escolar; Escolas; Práticas sociais e processos educativos; Jovem autor de ato infracional; School education and young offenders; Young offenders and school; Social practices and educational processes; CIENCIAS HUMANAS::EDUCACAO